Carbohydrate and Glycoconjugate Analysis by Ion Mobility Mass Spectrometry: Opportunities and Challenges - Huang, Yuting; S. Gelb, Abby; D. Dodds, Eric (Current Metabolomics, 2013)
Carbohydrates are characterized by a truly remarkable level of structural diversity which stands in accord with a corresponding functional diversity arguably unsurpassed by any other class of biomolecule. As metabolites, structural components, mediators of molecular interaction, and modifiers of other biomolecules, carbohydrates play central roles in numerous areas of biochemistry. Detailed molecular characterization of these classes of compounds poses a number of significant analytical challenges, a number of which arise from carbohydrate isomerism combined with the ability of monosaccharides to serve as the basis for branched oligosaccharide structures. Ion mobility spectrometry (IMS) represents a particularly appealing analytical methodology for addressing such hurdles. Because IMS provides for separation of gasphase ions according to their “shape to charge ratios,” this approach is well-suited to provide for the recognition, distinction, and resolution of isomeric carbohydrates and glycoconjugates. IMS is also readily coupled to well-established mass spectrometry ionization methods and analyzers, which provide complementary information on mass to charge ratios and allow tandem mass spectrometry dissociation experiments which can supply further structural information. Here, we offer a brief introduction to carbohydrate structure and diversity (including monosaccharides, oligosaccharides, and glycoconjugates thereof), followed by an overview of relevant IMS techniques (drift tube ion mobility spectrometry; high-field asymmetric waveform ion mobility spectrometry; and traveling wave ion mobility spectrometry). We then provide an overview of the literature on IMS as applied to the study of free carbohydrates (including isomer separation and general structural characterization) and glycoconjugates (including released glycans and intact glycoconjugates).
Keywords: glycopeptides